Analyses of the effect of cycle inlet temperature on the precooler and plant efficiency of the simple and intercooled helium gas turbine cycles for generation IV nuclear power plants - Gad-Briggs, Arnold; Nikolaidis, Theoklis; Pilidis, Pericles (MDPI, 2017)
Nuclear Power Plant (NPP) precooler coolant temperature is critical to performance because it impacts the work required to increase the coolant pressure. Variation of the coolant temperature results in varied precooler hot gas temperatures, which are cooled before re-entry. For recirculation, the heat sink (usually sea water), could exit the precooler at unfavourable temperatures and impact the re-entering coolant, if not recirculated properly at the source. The study objective is to analyse the effects of coolant inlet temperature on the heat sink and cycle efficiency. The cycles are Simple Cycle Recuperated (SCR), Intercooler Cycle Recuperated (ICR), and Intercooled Cycle without Recuperation (IC). Results show that the co-current precooler provides favourable outlet heat sink temperatures but compromises compactness. For a similar technology level, the counter-current precooler yields excessive heat sink outlet temperatures due to a compact, robust, and efficient heat transfer design, but could be detrimental to precooler integrity due to corrosion, including the cycle performance, if not recirculated back into the sea effectively. For the counter-current, the ICR has the best heat sink average temperature ratio of 1.4; the SCR has 2.7 and IC has 3.3. The analyses aid the development of Gas Cooled Fast Reactors (GFRs) and Very High Temperature Reactors (VHTRs), where helium is used as the coolant.
Keywords: Gen-IV; efficiency; NPP; cycle; precooler; performance; simple; intercooled; recuperated